Erectile Dysfunction in Men With Angiographically Documented Coronary Artery Disease - Foroutan, Seyed Kazem; Rajabi, Mohammadreza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; @font-face font-family:Stratford-DemiBold; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:131 0 0 0 9 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: We evaluated erectile function of men with coronary artery disease (CAD) and the relation between the degree of erectile dysfunction (ED) and the extent of coronary artery stenosis on cardiac angiography. Materials and Methods: Nondiabetic men with CAD documented by angiography were evaluated for ED. Erectile function was assessed by a 5-item version of the International Index of Erectile Dysfunction, the Sexual Health Inventory for Men (SHIM). Results: Of 401 men, 186 (46.4%) had ED (SHIM score, 21 or less). Men with ED were more likely to have more than 1 stenotic cardiac vessel (P < .001). The mean SHIM score was 20.9 Â± 7.6, 12.9 Â± 9.2, and 14.3 Â± 9.1 for men with 1-, 2-, and 3-vessel disease, respectively (P < .001). Multivariate analysis showed that only the SHIM score had a relationship with the number of involved vessels (P < .001); the SHIM score was lower and ED was more frequent in men with more than 1 vessel involvement. Forty-one patients (19.1%) without ED and 45 (24.2%) with ED had a positive history of myocardial infarction (P = .21). Symptoms of ED had appeared prior to CAD detection in 78 out of 189 patients (41.9%) with a mean time interval of about 23 months (range, 10 to 36 months). Conclusion: Our finding showed that the prevalence of ED is relatively high in patients with CAD, and has a relationship with the extent of CAD. Furthermore, ED may occur before CAD with an average interval of 2 years.